Sensitive Techniques for POCT Sensing on the Residues of Pesticides and Veterinary Drugs in Food - Liu, Lin; Gao, Yueying; Liu, Jinghan; Li, Ying; Yin, Ziye; Zhang, Yuanyuan; Pi, Fuwei; Sun, Xiulan (Bulletin of environmental contamination and toxicology, 2021)
For the immense requirement on agriculture and animal husbandry, application of pesticides and veterinary drugs had become a normal state in the farming and ranching areas. However, to intently pursue the yields, large quantities of residues of pesticides and veterinary drugs have caused serious harm to both the environment and the food industry. To control and solve such an issue, a variety of novel techniques were developed in recent years. In this review, the development and features about point-of-care-testing (POCT) detection on the residues of pesticides and veterinary drugs, such as, electrochemistry (EC), enzyme-linked immunosorbent assay (ELISA) and nano-techniques, were systematically introduced. For each topic, we first interpreted the strategies and detailed account of such technical contributions on detection and assessment of the residues. Finally, the advantages and perspectives about mentioned techniques for ultrasensitive assessment and sensing on pesticides and veterinary drugs were summarized.